Metal-Free Synthesis of 2-Substituted Quinazolines via Green Oxidation of o-Aminobenzylamines: Practical Construction of N-Containing Heterocycles Based on a Salicylic Acid-Catalyzed Oxidation System - Yamamoto, Yuki; Yamakawa, Chihiro; Nishimura, Riku; Dong, Chun-Ping; Kodama, Shintaro; Nomoto, Akihiro; Ueshima, Michio; Ogawa, Akiya (Frontiers in Chemistry, 2022)
Conventional quinazoline synthesis methods involve a highly multistep reaction, and often require excess amounts of substrate to control the product selectivity, leading to significant resource wastage. Hence, in this study, from the viewpoint of green chemistry, we developed a novel metal-free synthetic method for 2-substituted quinazoline derivatives by the 4,6-dihydroxysalicylic acid-catalyzed oxidative condensation of o-aminobenzylamines and benzylamines using atmospheric oxygen. In this system, the use of a catalytic amount of BF3‧Et2O (10 mol%) as a Lewis acid successfully led to the efficient oxidative condensation and intramolecular cyclization of these amines, followed by aromatization to afford the corresponding 2-arylquinazolines in up to 81% yield with excellent atom economy and environmental factor. Furthermore, to expand this green oxidation method to gram-scale synthesis, we investigated the development of an oxidation process using salicylic acid itself as an organocatalyst, and established a method for the practical green synthesis of a series of nitrogen-containing heterocycles. We expect that the findings will contribute to the development of practical synthesis methods for pharmaceutical manufacturing and industrial applications, along with further advancements in green chemistry.